Overview of Logistics Management at Niko Pharmacy on Jl. Besar Tj. Anom, Sembahe Baru, Pancur Batu District, Deli Serdang Regency, North Sumatra - Nur Afini Turnip; Amanda Aqiilah; Azzahra Khairani Siregar; Lisca Amalia Putri Br Sinaga; Rintan Arzeti; Rapotan Hasibuan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Drug logistics management is an important part of pharmaceutical services to ensure the availability, quality, and safety of drugs. This study aims to describe the implementation of drug logistics management at Niko Pharmacy, Pancur Batu District, Deli Serdang Regency. The study used a qualitative method with a descriptive design. Data were obtained through in-depth interviews and observations of pharmacy owners and pharmacy staff. Aspects studied included planning, budgeting, procurement, storage, distribution, disposal and destruction, recording and reporting, and monitoring and evaluation. The results showed that most drug logistics management activities have been running well. Planning is carried out based on sales data, prescriptions, and patient needs, while drug storage has implemented the FEFO system. Distribution, recording, and monitoring are carried out routinely to maintain drug availability. However, several obstacles were still found, such as budget limitations, delays in drug delivery, manual recording, and the lack of documentation of destruction activities and the results of monitoring and evaluation. Overall, drug logistics management at Niko Pharmacy has been implemented well, but it is necessary to strengthen the documentation and administration system to improve the quality of pharmaceutical services and support the sustainability of optimal drug logistics management.